2021
DOI: 10.3390/biom11071002
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Dementia: Gaining Insight through Circadian Clock Gene Pathways

Abstract: Neurodegenerative disorders affect fifteen percent of the world’s population and pose a significant financial burden to all nations. Cognitive impairment is the seventh leading cause of death throughout the globe. Given the enormous challenges to treat cognitive disorders, such as Alzheimer’s disease, and the inability to markedly limit disease progression, circadian clock gene pathways offer an exciting strategy to address cognitive loss. Alterations in circadian clock genes can result in age-related motor de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 252 publications
(326 reference statements)
0
20
0
Order By: Relevance
“…However, our analysis suggested that none of the demographic and intervention-associated factors were potential moderators influencing the effects of phototherapy on cognitive improvement. Moreover, decreased amplitude and robustness of circadian activity rhythm along with delayed rhythm might be the underlying mechanisms of cognitive decline (Maiese, 2021) and might be associated with an increased risk of developing dementia and mild cognitive impairment (Tranah et al, 2011). Although the circadian rhythm has emerged as a critical factor for patients with dementia (Slats et al, 2013;Kumar et al, 2022), our meta-regression did not show preferred recommendations among morning, afternoon, or individualized rhythm.…”
Section: Influence Of Moderatorsmentioning
confidence: 60%
“…However, our analysis suggested that none of the demographic and intervention-associated factors were potential moderators influencing the effects of phototherapy on cognitive improvement. Moreover, decreased amplitude and robustness of circadian activity rhythm along with delayed rhythm might be the underlying mechanisms of cognitive decline (Maiese, 2021) and might be associated with an increased risk of developing dementia and mild cognitive impairment (Tranah et al, 2011). Although the circadian rhythm has emerged as a critical factor for patients with dementia (Slats et al, 2013;Kumar et al, 2022), our meta-regression did not show preferred recommendations among morning, afternoon, or individualized rhythm.…”
Section: Influence Of Moderatorsmentioning
confidence: 60%
“…We then measured key proteins involved in the circadian clock rhythm pathways, including SIRT1, BMAL1, CLOCK, PER2, CRY1, CRY2 and REV-ERBα. 20 CLOCK and CRY1 protein expression from the YAGE group were significantly reduced…”
Section: Protein Expression Associated With Neuro-inflammation and Ci...mentioning
confidence: 96%
“…14 Circadian rhythm clock genes also play a critical role during cognitive dysfunction. 20 Furthermore, there was evidence suggesting a general link between neuro-inflammation and disruption of circadian time keeping during cognitive impairment. 21,22 Likewise, gut microbiota, and their associated microbiome, are important in the regulation of brain activity and cognition function.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the disruption of the circadian clock can be detrimental for many physiological functions, including depression [567,568], metabolic and cardiovascular diseases [569], and cancer [570,571]. It is also known that the circadian clock controls physiological processes such as brain metabolism, ROS homeostasis, hormone secretion, autophagy and stem cell proliferation, which are correlated with ageing, memory formation, and neurodegenerative and sleep disorders [572][573][574][575][576]. In Drosophila, the circadian clock regulates the timing of eclosion, courtship, rest, activity and feeding; it also influences daytime colour [577] and temperature preference [578].…”
Section: Magnetic Field and Lithium Effects On The Circadian Clockmentioning
confidence: 99%